Next-generation sequencing reveals germline mutations in an infant with synchronous occurrence of nephro- and neuroblastoma. (18th May 2016) - Theruvath, Johanna; Russo, Alexandra; Kron, Bettina; Paret, Claudia; Wingerter, Arthur; El Malki, Khalifa; Neu, Marie A.; Alt, Francesca; Staatz, Gundula; Stein, Raimund; Seidmann, Larissa; Prawitt, Dirk; et al.
ABSTRACT: Although neuro- and nephroblastoma are common solid tumors in children, the simultaneous occurrence is very rare and is often associated with syndromes. Here, we present a unique case of synchronous occurrence of neuro- and nephroblastoma in an infant with no signs of congenital anomalies or a syndrome. We performed genetic testing for possible candidate genes as underlying mutation using the next-generation sequencing (NGS) approach to target 94 genes and 284 single-nucleotide polymorphisms (SNPs) involved in cancer. We uncovered a novel heterozygous germline missense mutation p.F58L (c.172T→C) in the anaplastic lymphoma kinase ( ALK ) gene and one novel heterozygous rearrangement Q418Hfs * 11 (c.1254_1264delins TTACTTAGTACAAGAACTG) in the Fanconi anemia gene FANCD2 leading to a truncated protein. Besides, several SNPs associated with the occurrence of neuroblastoma and/or nephroblastoma or multiple primary tumors were identified. The next-generation sequencing approach might in the future be useful not only in understanding tumor etiology but also in recognizing new genetic markers and targets for future personalized therapy.